Diagnostic Efficacy of CT Scan and Ultrasonography in Identifying Hepatic Metastases from GI Cancers: A Histopathological Perspective (East West Medical College Journal, 2026)
Background: Hepatic metastases are common in advanced gastrointestinal (GI) tract cancers and significantly influence staging, treatment decisions, and prognosis. Accurate detection is of prime significance, with computed tomography (CT) and ultrasonography (USG) being the most common diagnostic tools. This study was conducted to evaluate the diagnostic efficacy of USG versus CT in detecting hepatic metastases from GI tract cancers, taking histopathology as the reference standard. Methods: This cross-sectional study was carried out in the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU) from October, 2018 to September, 2019. Total 50 adult patients with suspected hepatic metastases from diagnosed case of GIT cancer and patients undergoing surgery were included in this study. Result: The mean age was 57.9 years, with most patients aged 50–59 (34%) and predominantly male (66%). Histopathology confirmed hepatic metastases in 94% of cases. USG achieved a sensitivity of 89.36%, specificity of 66.67%, accuracy of 88%, PPV of 97.67%, and NPV of 28.57%. CT demonstrated superior sensitivity (95.74%), specificity (83.33%), accuracy (94.34%), PPV (97.83%), and NPV (71.43%). A significant association between CT and USG findings was observed (p = 0.001), though CT showed fewer false negatives. Conclusion: CT outperformed USG in detecting hepatic metastases from GI cancers, particularly in specificity and NPV, making it more reliable for ruling out disease. USG remains a valuable initial screening tool, with its diagnostic yield potentially improved through contrast enhancement.EWMCJ Vol. 14, No. 2, July 2026: 135-141